PENDIDIKAN VOKASIONAL (ALTERNATIF PENGEMBANGAN SDM DI INDONESIA) - Arif Ridha (Sekolah Tinggi Ilmu Tarbiyah (STIIT) Ahlussunnah Bukittinggi, 2021)
Vocational education provides training to develop human resources so that they are able to independently actualize themselves in developing all their potential and natural potential of Indonesia so that they are able to escape from the confinement of western capitalism. The problem then is whether vocational education has accommodated all the needs of the Indonesian people globally? This analytical study will try to unravel how vocational education (in this case is SMK) is expected, so that human resources are no longer used as their workers, with hard work sweating but the results are enjoyed by other countries, while we really really harmed.